2018
DOI: 10.1155/2018/2353280
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Manufacturing Process of Bee Venom Pharmacopuncture Containing Melittin as the Active Ingredient

Abstract: Background Pharmacopuncture is a unique treatment in oriental medicine that combines chemical stimulation with conventional acupuncture. However, there are no standardized methods for preparing the herbal medicines used in pharmacopuncture, and it is not clear whether the active ingredients are safe and stable. Several studies have investigated nonstandardized preparation processes, but few investigations have addressed safety and preparation methods. Pharmacopuncture may provide an alternative treatment for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…In addition, bee products can be safely consumed after adequate processing. Processing involves removal of known allergens such as enzyme treatment of royal jelly and filtration of bee venom by stepped-gradient open column [ 2 , 94 ].…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
“…In addition, bee products can be safely consumed after adequate processing. Processing involves removal of known allergens such as enzyme treatment of royal jelly and filtration of bee venom by stepped-gradient open column [ 2 , 94 ].…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
“…Melittin is one of the main elements from A. mellifera venom [ 3 ], making up 40%–60% of its completely dry weight, it takes the major biological part in BV. This linear peptide contains 26 amino acids (NH2-GIGAVLKVLTTGLPALISWIKRKRQQ-CONH2) [ 27 ].…”
Section: Pharmacological Mechanisms Of the Most Abundant Componentmentioning
confidence: 99%
“…BV therapy has been used for treating immunological diseases for many years. Recently, researchers have found that PLA2, which makes up 10%–12% of dry BV [ 3 ], has an immunomodulatory effect. Research has proven that regulatory T cells (Treg) can alleviate the development of autoimmune diseases [ 34 , 35 ] by promoting CD4 + CD25 + Treg cell differentiation ( Figure 2 ) [ 35 ].…”
Section: Pharmacological Mechanisms Of the Most Abundant Componentmentioning
confidence: 99%
See 2 more Smart Citations